DINAMIKA PENENTUAN AWAL BULAN KAMARIAH MENURUT MUHAMMADIYAH (STUDI ATAS KRITERIA WUJûD AL HILâL DAN KONSEP MAţLA’) - Amri, Rupii (At-Taqaddum, 2012)
Muhammadiyah used hisab hakiki wujud al-Hilal (The existence of crescent above the horizon) in determining the beginning of kamaria month. The use of this menthod sometimes has impacted in deciding the time for Ramadan, Idul Fitri and Idul Adha the results, sometimes, differ from the government and other Islamic organization?s conclusions. This research is to answer following questions 1) Why does Muhammadiyah use hisab hakiki wujud al-hilal to determine the beginning of kamaria month?, 2) How are the position of mathla? and date line used by Muhammadiyah in determining the beginning of kamaria months if data line separate Indonesian area?, 3) How does Muhammadiyah justify wujud al-halal concept that meets with astronomical criteria?This research is a qualitative library research based. The method for collecting data is a document study and interview, while descriptive analysis is choosen for the method for data analysis. Ushul al-fiqh and scientific cum-doctriner approaches are also used as supporting tools for the data analysis. The research shows several interesting results. First, the decision of Muhammadiyah to use hisab hakiki wujud al-hilal is basically shaped by Muhammadiyah?s understanding on Islamic tradition. Second, mathla? that has taken by Muhammadiyah as parameter is mathla? wilayah al-hukm (all of Indonesia area). Third, reorientation of Muhammadiyah to justifies or to match wujud al-hilal criteria with astronomical criteria, namely crescent visibility according to international criteria, so far, has not been officially decided yet. The idea still runs as discource among Muhammadiyah?s leaders.